Day of Week Effects In Indian Stock Market: an Empirical Study: An investigation into week day effects in the Indian stock market (Journal of Advances and Scholarly Researches in Allied Education, 2014)
There are manytypes of anomalies in the financial markets e.g. technical anomalies,fundamental anomalies and calendar anomalies. The area of research taken inpresent study focuses on calendar anomalies only. There have been intensivestudies over all these anomalies and literature is full of empirical evidences.Calendar anomalies involve patterns in stock returns from year to year or monthto month, while technical anomalies include momentum effect. Weed day effectscomes under the most popular calendar anomalies. The present paper does anempirical analysis of the week day effects in the Indian stock market. The datahas been taken from BSE Sensex (a basket of 30 stocks), widely accepted as thetrue representative of the Indian stock market. The data taken for the study isdivided into three phases viz. (i) 1998 to 2001, (ii) 2002 to 2007 (iii) 2010to 2012. Years 2008 and 2009 have been excluded from the study being of highfluctuations. The data has been analyzed with the help of descriptivestatistics, t-test and ANOVA. The results show that the week day effect existsonly before rolling settlement viz. 1998 to 2001. No week day effect exitsduring the rest of the two periods viz. 2002 to 2007 and 2010 to 2012.